IMPROVEMENT OF THE ECONOMIC MECHANISM OF ENSURING ENVIRONMENTAL SAFETY IN THE PRODUCTION OF INDUSTRIAL ENTERPRISES - Olloboyeva Lobar Ro’zi qizi; Mamaraimova Hilola Abduqahhor qizi (Scholars Digest Publishing, 2023)
Hazard: A hazard is anything that has the potential to cause harm to human health or the environment. • Risk: Risk is the likelihood that a hazard will cause harm. • Control: Control is any action taken to reduce the risk of harm from a hazard. Environmental safety is about identifying and controlling hazards to protect human health and the environment. This can be done through a variety of methods, including: • Engineering controls: These are physical or technological measures that are designed to prevent or reduce exposure to hazards. For example, engineering controls could include installing ventilation systems to remove harmful fumes or using safety equipment to protect workers from exposure to hazardous chemicals. • Administrative controls: These are procedures and policies that are designed to prevent or reduce exposure to hazards. For example, administrative controls could include requiring workers to wear personal protective equipment or providing training on safe work practices. • Personal protective equipment: This is equipment that is worn by workers to protect them from exposure to hazards. For example, personal protective equipment could include safety glasses, gloves, and respirators. Environmental safety is an important part of any workplace. By identifying and controlling hazards, we can help to protect human health and the environment.
Keywords: Hazard, Risk, Control, Engineering controls, Administrative controls, Personal protective equipment, Chemical hazards, Physical hazards, Biological hazards, Ergonomic hazards, Environmental hazards, Cleaner technologies, Reduced environmental impact, Employee education.